Building the Composite Face Lift: A Personal Odyssey. Issue 1 (July 2016) - Hamra, Sam T.
Abstract : Summary: This article is a 42-year history of the development of a comprehensive face-lift technique by the author. It describes how the composite rhytidectomy has been constructed, anatomical area by anatomical area, over the author's lifetime career as a plastic surgeon. Over the course of these years, beginning with Skoog's 1973 description of using the platysma muscle of the lower face, it describes how progressively the other significant structures of anatomy necessary to be used in achieving significant rejuvenation have been analyzed by the author and in turn surgically repositioned. The theory was based on creating a composite flap of the face, keeping the orbicularis oculi muscle, facial platysma muscle, and cheek fat in their normal anatomical and intimate relationship with each other by using the skin as the carriage. In addition, differences of vectors between the composite rhytidectomy and traditional techniques are demonstrated. The gradual and persistent pursuit of periorbital rejuvenation using the lower eyelid fat and the septal orbitale is described. Each of the anatomical structures involved and the description of their importance and surgical execution have been published over the surgical career of the author, including use of the same principles for reversing suboptimal face-lift results. Abstract : This and Related "Classic" Articles Appear on Prsjournal.Com for Journal Club Discussions.